2021
DOI: 10.1371/journal.pone.0245653
|View full text |Cite
|
Sign up to set email alerts
|

Pten regulates collagen fibrillogenesis by fibroblasts through SPARC

Abstract: Collagen deposition contributes to both high mammographic density and breast cancer progression. Low stromal PTEN expression has been observed in as many as half of breast tumors and is associated with increases in collagen deposition, however the mechanism connecting PTEN loss to increased collagen deposition remains unclear. Here, we demonstrate that Pten knockout in fibroblasts using an Fsp-Cre;PtenloxP/loxP mouse model increases collagen fiber number and fiber size within the mammary gland. Pten knockout a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
(95 reference statements)
2
9
0
Order By: Relevance
“…Thus, the distinction between secretion of soluble collagen and fibril assembly is important in studies of disease, in which simple measurement of collagen expression or secretion does not equate to fibrogenesis. This distinction between collagen secretion and assembly was also suggested in a recent study on Pten- knockout mammary fibroblasts, where SPARC affects collagen fibrillogenesis and not secretion, acting through fibronectin 49 . Of note, whilst SPARC and fibronectin were detected in our previously-reported time-series mass spectrometry analyses (in the SLDOC soluble fraction and high-salt insoluble fractions respectively), they were not circadian clock rhythmic 13 .…”
Section: Discussionsupporting
confidence: 57%
“…Thus, the distinction between secretion of soluble collagen and fibril assembly is important in studies of disease, in which simple measurement of collagen expression or secretion does not equate to fibrogenesis. This distinction between collagen secretion and assembly was also suggested in a recent study on Pten- knockout mammary fibroblasts, where SPARC affects collagen fibrillogenesis and not secretion, acting through fibronectin 49 . Of note, whilst SPARC and fibronectin were detected in our previously-reported time-series mass spectrometry analyses (in the SLDOC soluble fraction and high-salt insoluble fractions respectively), they were not circadian clock rhythmic 13 .…”
Section: Discussionsupporting
confidence: 57%
“…MiR-29c-5p might also target PTEN. Low stromal PTEN expression is associated with multiple cancers, but also with high mammographic density through collagen deposition [ 44 ]. Murine PTEN knockout models demonstrate more collagen secretion, fiber formation and increased expression of the ECM regulator SPARC [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low stromal PTEN expression is associated with multiple cancers, but also with high mammographic density through collagen deposition [ 44 ]. Murine PTEN knockout models demonstrate more collagen secretion, fiber formation and increased expression of the ECM regulator SPARC [ 44 ]. Furthermore, a mouse model with fibroblast-specific PTEN deletion resulted in an alteration of collagen organization, a promotion of collagen orientation in surrounding tumors, and an enhancement of highly aligned matrices when comparing with a wildtype model [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…To eliminate these costly and time-consuming immunostaining steps and to enable visualization of the matrix for the screening platform, cells were cultured with exogenous fluorescein-labeled fibronectin. Previous studies have demonstrated the incorporation of fluorescent fibronectin into cell-derived matrices (74,75), and the addition of exogenous fluorescent fibronectin has previously been used to study fibronectin fibrillogenesis (62,76). Furthermore, fibronectin is oriented in an equivalent manner as collagen and is the most prevalent protein expressed in CDM (1).…”
Section: Miniaturization and Streamlining Of The Matrix Organization ...mentioning
confidence: 99%
“…In vivo ablation of Pten (Fsp-Cre;Pten loxP/loxP ) in fibroblasts of mouse mammary tissue led to increased collagen deposition, collagen alignment, and tumorigenesis in the presence of the Neu oncogene (58,63). In vitro, CDM produced by Pten null (Pten -/-) murine mammary fibroblasts results in a highly organized, aligned matrix compared to the largely disorganized matrix produced by Pten intact (wild type) fibroblasts (63,75). As such, these cells are well suited for screening compounds that can 'normalize' a highly aligned matrix.…”
Section: Kinase Inhibitor Screen Identifies Novel Regulators Of Matri...mentioning
confidence: 99%